Bombay Islam: the religious economy of the West Indian Ocean, 1840 - 1915 - Green, Nile (Cambridge University Press, 2011)
"As a thriving port city, nineteenth-century Bombay attracted migrants from across India and beyond. Nile Green's Bombay Islam traces the ties between industrialization, imperialism, and the production of religion to show how Muslim migration from the oceanic and continental hinterlands of Bombay in this period fueled demand for a wide range of religious suppliers, as Christian missionaries competed with Muslim religious entrepreneurs for a stake in the new market. Enabled by a colonial policy of non-intervention in religious affairs, and powered by steam travel and vernacular printing, Bombay's Islamic productions were exported as far as South Africa and Iran. Connecting histories of religion, labour, and globalization, the book examines the role of ordinary people mill hands and merchants in shaping the demand that drove the market. By drawing on hagiographies, travelogues, doctrinal works, and poems in Persian, Urdu, and Arabic, Bombay Islam unravels a vernacular modernity that saw people from across the Indian Ocean drawn into Bombay's industrial economy of enchantment"--